The Systematic Oppression of Afghan Women and Girls Since the Taliban’s Takeover in 2021 - Javed, Setara; Quraishi, Tamanna; Nargis Hakimi (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study examines the impact of the Taliban's policies on Afghan women's access to education, employment, and public participation since their return to power in 2021. By conducting a systematic literature review of peer-reviewed articles, reports, and academic papers published between 2021 and 2024, the research identifies key barriers Afghan women face in these critical areas. The review draws data from several reputable databases including Google Scholar, JSTOR, Scopus, PubMed, and SpringerLink. The findings reveal significant setbacks in women's rights, with strict restrictions on education, limited employment opportunities, and reduced participation in public life. The analysis also highlights the broader socio-economic and psychological consequences of these policies, emphasizing the detrimental impact on Afghanistan's development and international relations. The study calls for targeted international interventions, humanitarian support, and policy changes to address the gender-based discrimination imposed by the Taliban. Recommendations include sanctions against Taliban leadership, expansion of scholarship programs for Afghan women, support for Afghan-led advocacy movements, and the establishment of economic empowerment initiatives. The findings underscore the importance of international solidarity in restoring Afghan women's rights and freedoms.